2015
DOI: 10.3748/wjg.v21.i20.6206
|View full text |Cite
|
Sign up to set email alerts
|

Expression of COX-2 and HER-2 in colorectal cancer and their correlation

Abstract: COX-2 and HER-2 are important markers for invasion and metastasis of colorectal cancer, and they act together to regulate the invasion and metastasis of colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
34
3
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 24 publications
9
34
3
2
Order By: Relevance
“…Li et al (2014) by their meta-analysis, stated that HER2/neu overexpression probably has little impact on CRC survival (6). Recently another meta-analysis revealed that no correlation existed between HER2/neu expression and clinicopathological features including tumor location, grade of differentiation, TNM stages and lymph node metastasis (28). In our study, there was also no significant association between HER2/neu over expression and clinicopathological parameters (age, gender, size, location of tumor, tumor grade and stage).…”
Section: Discussioncontrasting
confidence: 34%
See 1 more Smart Citation
“…Li et al (2014) by their meta-analysis, stated that HER2/neu overexpression probably has little impact on CRC survival (6). Recently another meta-analysis revealed that no correlation existed between HER2/neu expression and clinicopathological features including tumor location, grade of differentiation, TNM stages and lymph node metastasis (28). In our study, there was also no significant association between HER2/neu over expression and clinicopathological parameters (age, gender, size, location of tumor, tumor grade and stage).…”
Section: Discussioncontrasting
confidence: 34%
“…So it is unclear whether HER2/neu is a potential therapeutic target or/and a prognostic marker in patients with CRC or not (23,(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…Largest number of colorectal patients are in age range of 21-40 years ( Figure: 1). In our study, 80% cases of colorectal carcinomas showed varying degree of cytoplasmic COX-2 positivity which corresponded very much to the findings of Wu et al in 2015 [6] who had similar observation of overexpression of COX-2 in 77.97% cases of colonic adenocarcinomas. In our study, 71.42% cases of well-differentiated adenocarcinoma of colorectum showed positivity for COX-2 ( Figure: 2 & 3), whereas all cases of moderately ( Figure: 4) and poorly differentiated adenocarcinoma of colorectum showed positivity for COX-2 (Table: 1).…”
Section: Resultssupporting
confidence: 78%
“…A COX-2 increased expression has been seen in many tumors, including CRC [22]. In detail, an enhanced expression of COX-2 was detected in 77% of cases of CRC as compared with the normal surrounding mucosa [23].…”
Section: In Vitro Studies: the Effect Of Curcumin On Colon Cancer Celmentioning
confidence: 91%
“…Another study by Watson et al about curcumin cytotoxicity on HCT-116 and HT29 cell lines revealed that a sequential time and dose dependent inhibition of cell proliferation was observed when p53 was upregulated [21].As reported above, one of the main mechanisms through which curcumin blocks cell growth is the induction of apoptosis. This process in the CRC cells involves multiple molecular targets including enzymes (cyclooxygenase-2 (COX 2)), transcription factors (NF-kB and beta-catenin), Bcl-2 family members (Bcl-2, Bax, and Bcl-xL), death receptors (death receptor 5 (DR5) and Fas), protease enzymes (caspase 3 and caspase 8), and ROS.A COX-2 increased expression has been seen in many tumors, including CRC [22]. In detail, an enhanced expression of COX-2 was detected in 77% of cases of CRC as compared with the normal surrounding mucosa [23].…”
mentioning
confidence: 99%